A Pipeline Transport Model for the Economic Analysis of a Green Hydrogen Production System - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2024)
In recent years, Chile has become a focus of study for green hydrogen projects due to its high potential for renewable energy and its commitment to decarbonizing the energy matrix through already established public policies. This document presents an optimization model for the transportation of green hydrogen through pipelines using the simulation of a hydrogen production system model in the Antofagasta region, specifically in the Atacama Desert. The results show that the best option for transporting hydrogen from the production plant to the export port is through pipelines, which should be sized to a diameter of 0.15 m. © 2024 IEEE.
Keywords: hydrogen; solar power; renewable energies; hydrogen export; hydrogen cost